Cyber Da’wa of “Aa Gym Daily Vlog” as Moslem Moderate Preaching Medium - Supratman, Lucy Pujasari; Wahyudin , Aep (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
New media plays a big role in virtual da’wa for society in a disruption era.